Long-Term Patient Satisfaction with Thermal Balloon Ablation for Abnormal Uterine Bleeding - Penezic, Lindsey (Society of Laparoendoscopic Surgeons, 2014)
BACKGROUND AND OBJECTIVE: Thermal balloon ablation is a minimally invasive surgical technique that can be used to treat abnormal uterine bleeding/heavy menstrual bleeding (AUB/HMB). Most published studies to date provide information on short-term patient satisfaction and outcomes. The purpose of this study was to determine long-term patient satisfaction after thermal balloon endometrial ablation 7 to 10 years postoperatively in a population previously surveyed at the Penn State Milton S. Hershey Medical Center at 1 to 5 years postoperatively. METHODS: Two-hundred fourteen patients were identified who underwent thermal balloon ablation at our institution between January 1, 2001 and December 31, 2004. These patients were mailed a 2-page survey asking for information on demographics, patient satisfaction, postoperative bleeding patterns, and the need for subsequent surgery. Satisfaction rates, amenorrhea rates, and the rates of women who required hysterectomy were calculated as percentages. RESULTS: Ninety-seven patients returned completed surveys. The survey response rate was 62%, excluding 57 surveys that were returned as undeliverable. The follow-up interval was 93 to 129 months. Eighty-seven percent of respondents were satisfied with the results of their procedure compared with 88% in the original study. Subsequent hysterectomy was required in 21.6% of women after 7 to 10 years compared with 9% after the 1- to 5-year follow-up period. Of the 76 women who did not undergo hysterectomy, 58% reported amenorrhea and 35.5% reported minimal to light bleeding. CONCLUSION: This study demonstrates a consistently high patient satisfaction rate with thermal balloon ablation at our institution at 7 to 11 years postoperatively compared with 1 to 5 years postoperatively. The hysterectomy rate, however, was 2.4 times greater in the long-term follow-up period.